2007
DOI: 10.1007/s00221-007-0862-y
|View full text |Cite
|
Sign up to set email alerts
|

The increased foreperiod duration to attain the neutral optimal preparation from sitting to standing

Abstract: The purpose of the present experiment was to investigate the effects of a neutral preparation during the foreperiod on motor and postural programming processes in a voluntary upper limb movement. The foreperiod duration (300, 500, 700 and 900 ms) and the postural condition (sitting vs standing) were manipulated using a neutral preparation (no advanced information during the preparatory signal). Thirteen subjects performed a raising arm movement with 1 kg load at the wrist. Premotor time, latency of the anticip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…In this way, participants could gain time to prepare a delayed anticipatory postural synergy in order to react as fast as possible. A temporal modulation in the central organization of the postural command according to foreperiod duration is already known [13]. Nevertheless, a training induced modification in the level of alertness/readiness prior to the onset of the obstacle's motion was not shown in the present study to support this hypothesis.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…In this way, participants could gain time to prepare a delayed anticipatory postural synergy in order to react as fast as possible. A temporal modulation in the central organization of the postural command according to foreperiod duration is already known [13]. Nevertheless, a training induced modification in the level of alertness/readiness prior to the onset of the obstacle's motion was not shown in the present study to support this hypothesis.…”
Section: Discussioncontrasting
confidence: 68%
“…Moreover, improving the speed of visuo-motor processing afforded participants the opportunity for real time processing of the optical expansion information of the approaching object in order to tune response onset, eliminating reliance on anticipatory scaling. In addition to being safer for the elderly [4], this strategy seems to be energetically more efficient as it reduces the duration and level of activation associated with motor preparation of the response [13]. The benefits of visuo-motor practice have been stressed in studies showing that older adults who play tennis have better coincidence-timing accuracy [14] and collision avoidance skills [10] than their non-player counterparts.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Longer FP length did not influence front-leg knee and front-wrist joint RT, while it did influence shorter joint RT in the other joints. In a few studies, RT values produced a U-shaped curve with an optimal FP length (Yuanhui and Kasai, 1993; Cuisinier et al, 2007). Similarly, the front-leg knee and front-arm wrist joint RT created a U-shaped curve; longer these joint RT were not sensitively decreased in the L and LL conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous basic studies measuring surface EMG activity have revealed that the optimal FP length (with the shortest EMG latency) differs in accordance with the muscle (Yuanhui and Kasai, 1993; Cuisinier et al, 2007). For instance, in a single upper-limb movement, FP length affects EMG latencies for both the elector spinaes and contralateral tensor fascia lata; however, FP length does not affect latencies of both biceps femoris.…”
Section: Introductionmentioning
confidence: 99%